2014
DOI: 10.2174/1874453201407010049
|View full text |Cite
|
Sign up to set email alerts
|

Red-cockaded Woodpecker Microhabitat Characteristics and Reproductive Success in a Loblolly-Shortleaf Pine Forest

Abstract: Abstract:We investigated the relationship between red-cockaded woodpecker (Picoides borealis) reproductive success and microhabitat characteristics in a southeastern loblolly (Pinus taeda) and shortleaf (P. echinata) pine forest. From 1997 to 1999, we recorded reproductive success parameters of 41 red-cockaded woodpecker groups at the Bienville National Forest, Mississippi. Microhabitat characteristics were measured for each group during the nesting season. Logistic regression identified understory vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 13 publications
2
4
2
Order By: Relevance
“…if ≥ 1 egg lost), and the proportion of eggs lost. Our study and Wood et al (2014) found a similar negative relationship between RCW Dryobates borealis group density and egg loss. However, whereas other studies (McCormick et al 2003, Wood et al 2014) found a link between increased hardwood midstory and increased egg loss, we did not detect a relationship.…”
Section: Rcw Habitat and Partial Brood Loss In The Oakmulgeesupporting
confidence: 87%
See 4 more Smart Citations
“…if ≥ 1 egg lost), and the proportion of eggs lost. Our study and Wood et al (2014) found a similar negative relationship between RCW Dryobates borealis group density and egg loss. However, whereas other studies (McCormick et al 2003, Wood et al 2014) found a link between increased hardwood midstory and increased egg loss, we did not detect a relationship.…”
Section: Rcw Habitat and Partial Brood Loss In The Oakmulgeesupporting
confidence: 87%
“…Our study and Wood et al (2014) found a similar negative relationship between RCW Dryobates borealis group density and egg loss. However, whereas other studies (McCormick et al 2003, Wood et al 2014) found a link between increased hardwood midstory and increased egg loss, we did not detect a relationship. Interestingly, we did not find other studies in the literature that estimated relationships between partial brood loss and burn season.…”
Section: Rcw Habitat and Partial Brood Loss In The Oakmulgeesupporting
confidence: 87%
See 3 more Smart Citations